Wokół działalności wydawniczej oraz redakcyjnej bł. Edmunda Bojanowskiego - Rozwadowska, Marta Diana (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
This text is an attempt to show Edmund Bojanowski as editor and publisher. He knew that the only possible and sensible way to go would be organic work. He believed that every human being had the duty to enlighten other people and to preach the truth. He was aware of the times in which he had come to live, and therefore he wanted to refresh the hearts of people who were tired of struggles of insurrection, fighting, epidemics, subjected to the repression of the invader and often resigned and tired of life. He was sure that one of the best ways to reach as many people as possible would be to publish a magazine. Thanks to this he obtained not only the finances he devoted to orphans, but also could influence the education of readers. In this noble goal he created „Pokłosie. Zbieranka literacka na korzyść sierot” and „Rok Wiejski”: thematically differentiated and pictorial journals, but having a common purpose - mission of evangelization and help the neediest.